2016
DOI: 10.1177/1933719116641761
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum microRNA Profile by Solexa Sequencing in Women With Endometriosis

Abstract: Circulating miRNAs may be useful as detection biomarkers for the early diagnosis of minimal-mild endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 23 publications
1
64
0
Order By: Relevance
“…Many microRNAs have been investigated in the study of endometriosis. Wang et al . evaluated microRNA expression in serum samples from 30 women with minimal to mild endometriosis and 20 control women.…”
Section: Discussionmentioning
confidence: 99%
“…Many microRNAs have been investigated in the study of endometriosis. Wang et al . evaluated microRNA expression in serum samples from 30 women with minimal to mild endometriosis and 20 control women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the miRNAs obtainable from diseased tissues and other body fluids were able to detect various diseases. [ 40 ] Today, advances in sequencing and microarray technology have made it possible to investigate systemic levels of miRNAs [ 41 ] and long non-coding RNA. [ 42 ] Deregulation of miRNAs is involved in the pathophysiology of endometriosis and they have been investigated as potential biomarkers.…”
Section: New Molecular Signaturesmentioning
confidence: 99%
“…Studies investigating miRNA profiles in eutopic tissues from women with and without endometriosis [64], [65], [66] showed a trend of downregulated miRNA levels in tissues from women with endometriosis. Wang and colleagues also showed global downregulation in the circulating levels of miRNAs in the serum of women with endometriosis, with 91% of significantly differentiated miRNAs showing decreased expression in endometriosis patients [67]. There are very few studies that have measured miRNAs in the peritoneal fluid (PF), which is the most dynamic component and major player in the etiology of endometriosis [11], [68], [69].…”
Section: Introductionmentioning
confidence: 99%